2003
DOI: 10.1016/s0014-5793(03)00129-7
|View full text |Cite
|
Sign up to set email alerts
|

ATP‐induced, sustained calcium signalling in cultured rat cortical astrocytes: evidence for a non‐capacitative, P2X7‐like‐mediated calcium entry

Abstract: The receptor mechanisms regulating the ATP-induced free cytosolic Ca 2+ concentration ([Ca 2+ ] i ) changes in cultured rat cortical type-1 astrocytes were analyzed using fura-2-based Ca 2+ imaging microscopy. Upon prolonged ATP challenge (1^100 W WM), astroglial cells displayed a biphasic [Ca 2+ ] i response consisting of an initial peak followed by a sustained elevation. Suramin and pyridoxalphosphate-6-azophenyl-2P P,4P P-disulfonic acid blocked both components, albeit to a di¡erent extent. By contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 37 publications
4
60
1
Order By: Relevance
“…How do these results change when the desensitization effect of ATP receptors are included in the model? In fact, the data reported in Nobile et al [10] clearly show that the P2X receptor desensitizes when exposed for several seconds to ATP. Thus, a very simple model describing the desensitization process of the ionotropic purinergic receptor was introduced in the calcium model.…”
Section: Pyramidal Neuron and Astrocytementioning
confidence: 83%
See 4 more Smart Citations
“…How do these results change when the desensitization effect of ATP receptors are included in the model? In fact, the data reported in Nobile et al [10] clearly show that the P2X receptor desensitizes when exposed for several seconds to ATP. Thus, a very simple model describing the desensitization process of the ionotropic purinergic receptor was introduced in the calcium model.…”
Section: Pyramidal Neuron and Astrocytementioning
confidence: 83%
“…In Di Garbo et al [36], it was shown that the above model is capable of describing, both qualitatively and quantitatively, the experimental results reported in [10]. In particular, it was shown that the model is able to reproduce the ATP-evoked biphasic calcium response (the transient and the sustained phase) in the astrocyte: the transient phase corresponds to the release of calcium from the ER store, while the sustained part is mainly determined by the influx of extracellular calcium mediated by the P2X purinoreceptors.…”
Section: Biophysical Model Of Calcium Signaling In Astrocytesmentioning
confidence: 85%
See 3 more Smart Citations